Development and validation of a predictive nomogram for the pregnancy rate after tubal anastomosis in women with tubal ligation - Shanliang Shang; Wenhua Liu; Xiaona Lin (Laparoscopic, Endoscopic and Robotic Surgery)
Objective: Female sterilization is a common contraceptive method, but with changing family dynamics, an increasing number of women seek to restore fertility after tubal sterilization. Current clinical practice lacks effective tools for predicting pregnancy rates in this population after tubal anastomosis. This study aims to develop and internally validate a novel nomogram for predicting the pregnancy rate in women with tubal ligation after tubal anastomosis. Methods: We developed a prediction model based on a training dataset of 208 patients with tubal ligation after undergoing tubal anastomosis between January 2012 and August 2020 at Sir Run Run Shaw Hospital, Zhejiang University School of Medicine. The follow-up period for all patients was one year postsurgery, during which pregnancy outcomes were recorded. The LASSO regression model was used to optimize feature selection for the pregnancy rate risk model. The performance of the nomogram was assessed for its calibration, discrimination, and clinical usefulness. Internal validation was assessed. Results: Predictors included in the prediction nomogram were age, type of anastomosis, sterilization duration, time of conception, and anti-Mullerian hormone (AMH) levels. The model displayed good discrimination, with a C-index of 0.924 (95% CI: 0.876–0.971), and good calibration. A high C-index value of 0.879 was still reached in the interval validation. Decision curve analysis revealed that the pregnancy rate nomogram was clinically useful when intervention was selected at the pregnancy rate possibility threshold of 1%. Conclusion: This novel pregnancy rate nomogram incorporating age, type of anastomosis, sterilization duration, time of conception, and AMH could be conveniently used to predict the pregnancy rate in women with tubal ligation after tubal anastomosis.